Front Cover: Robust Macroscopic 3D Sponges of Manganese Oxide Molecular Sieves (Chem. Eur. J. 64/2017). Issue 64 (21st September 2017) - Liu, Zhenxin; Wu, Depeng; Guo, Xuehui; Fang, Shaoming; Wang, Lizhen; Xing, Yu; Suib, Steven L.
Abstract : Free‐standing 3D OMS‐2 sponges with controlled densities are presented. The 3D OMS‐2 sponges possess a combination of outstanding physical, mechanical, and electrical properties. Moreover, some of these properties have systematic trends with various densities. This study sheds new light on manipulating properties of such sponges through controlling sponge densities. These new materials are promising for various applications such as catalysis, sensing, energy storage, and environmental materials. More information can be found in the Full Paper by Z. Liu, Y. Xing et al. onpage 16213 .